Courtesy visit to the Attorney General of Malaysia, YBhg. Tan Sri Dato' Sri ldrus Harun - UiTM, Faculty of Law (Faculty of Law, 2022)
The Dean of the Faculty of Law, Assoc. Prof. Dr Hartini Saripan had accompanied the Deputy Vice-Chancellor (Industry, Community & Alumni Network (ICAN), UiTM, YBhg. Prof Dr Mohamad Hariri Abdullah to pay a courtesy visit to the Attorney General of Malaysia, YBhg. Tan Sri Dato' Sri ldrus Harun for the CEO@Faculty Programme 1.0: Learn Fram The Pros at the Attorney General's Chambers, Putrajaya. The meeting was also attended by the Solicitor General of Malaysia, YBhg. Datuk Ahmad Terrirudin Mohd Salleh, the Director of Industry Network Centre, UiTM, Prof. Dr Muhammad Hussain Ismail, and the Head of ICAN Communication Centre, UiTM, Dr Neesa Ameera Mohamed Salim. The meeting was on the CEO@Faculty Programme, an initiative to invite renowned industry leaders to share their industry knowledge, experiences and expertise with students in line with UiTM's objective of birthing competent and holistic graduates. Apart from that, the Dean discussed with the learned Attorney General to collaborate on future programmes to better expose law students of UiTMLaw to the legal industry.